Investigation on microstructure evolution and mechanical properties of Mg–Li–Al–Ca alloy after a series of heat treatments - Degao Qiao; Shiwen Dong; Cui Chen; Peng Peng; Xing Pei; Xiantao Yan; Wanchao Zheng; Hong Zhang; Jiatai Wang (Journal of Materials Research and Technology, 2023)
Four heat treatment process routes were designed to study the microstructure evolution and mechanical properties of Mg–Li–Al–Ca alloy in relation to the heat treatment process. After heat treatment (Mg,Al)2Ca phase decomposed, and Li element volatilized. A large number of fine α-Mg precipitated phases appeared in β-Li matrix. The optimum mechanical properties of heat-treated alloy were obtained at 350 °C for 120 min, which are 190 MPa and 12% for tensile properties and 507 MPa and 51.9% for compression properties. Segregation of Al and Ca element was observed at grain boundaries. The phase boundaries between newly precipitated α-Mg phase and β-Li matrix impeded the slip of dislocations. It is believed that both the precipitation strengthening due to the formation of α-phase and the solid solution strengthening enhanced by the decomposition of (Mg,Al)2Ca phase play crucial roles in the improvement of mechanical properties.